Analisis Pengaruh Rasio CAR, LDR, NPL dan BOPO terhadap Kinerja Keuangan (ROA) Bank HIMBARA Tahun 2017–2024 - Safitri, Meilina; Sumawidjaja, Riyandi Nur; Sofiati, Nunung Ayu; Ismail, Gurawan Dayona; Sudaryo, Yoyo (Akuntansi & Ekonomika, 2025)
This study aims to analyze whether the CAR, LDR, NPL, and BOPO ratios affect ROA. The financial ratio data were obtained from secondary data of HIMBARA banks (BRI, BNI, Mandiri, and BTN) for the 2017–2024 period. The data analysis method used was multiple linear regression with SPSS. The partial results show that CAR influences ROA, while LDR, NPL, and BOPO do not have a significant effect on ROA. Simultaneously, all independent variables have a significant effect on the dependent variable. The obtained Adjusted R Square indicates that CAR, LDR, NPL, and BOPO collectively explain 92.4% of the variation in ROA, while the remaining 7.6% is influenced by other factors. This research is expected to provide a useful reference for the public and future researchers in understanding the factors that influence bank profitability.